Les traductions de la Bible et l’évolution du malgache contemporain - Gueunier, Noël J. (Archives de sciences sociales des religions, 2009)
Bible translation has had a profound effect on the constitution and fixation of modern Malagasy language. The writing process began to be successful in a missionary period contemporary with the formation of a State power (1818-1895). The history of the translations and revisions of the Malagasy Bible shows how fundamental was the protestant work of translation for the national language. Choices made then persist in the Catholic version (published 1938) and even in the œcumenical translation (1991-2005). They all retain a "biblical language" now fixed. This may explain why the recent inter-confessional translation has not been well received. Paradoxically, as institutional œcumenism recedes, the two traditions, Protestant and Catholic often join together in customary events. Where the sociologist might be tempted to seek a syncretism, there appears to be rather an association and a negotiation between distinct traditions.